THE SKILL OF "TRANSFERING" EMOTIONS AND EXPERIENCES TO THE READER (Scientific journal of the Fergana State University, 2023)
This article examines the lyrical heritage of Academician G. Ghulam. In it, the impact of Bedil's creative work on G. Ghulam's lyrics is studied on the example of certain poems of the poet. The reasons for G. Ghulam's appeal to Bedil are analyzed on the basis of examples from the poet's work. Following his poems "Bog‘", "Sog‘inish", "Yangi Ishq", "Chaman", "San'atim" and a number of other poems, the researcher explains the reasons why G. Ghulam came to the conclusion that the human mind has a divine essence.   In the article, it is justified that conceptually important language expressions and poetic images in G. Ghulam's work are directly connected with the traditions of Eastern literature, in particular, Bedil's philosophical views. The previous comments were briefly summarized by the researcher.